Macrophage autophagy in macrophage polarization, chronic inflammation and organ fibrosis - Jun-Hao Wen; Dong-Yi Li; Shan Liang; Chen Yang; Ji-Xin Tang; Hua-Feng Liu (Frontiers in Immunology, 2022)
As the essential regulators of organ fibrosis, macrophages undergo marked phenotypic and functional changes after organ injury. These changes in macrophage phenotype and function can result in maladaptive repair, causing chronic inflammation and the development of pathological fibrosis. Autophagy, a highly conserved lysosomal degradation pathway, is one of the major players to maintain the homeostasis of macrophages through clearing protein aggregates, damaged organelles, and invading pathogens. Emerging evidence has shown that macrophage autophagy plays an essential role in macrophage polarization, chronic inflammation, and organ fibrosis. Because of the high heterogeneity of macrophages in different organs, different macrophage types may play different roles in organ fibrosis. Here, we review the current understanding of the function of macrophage autophagy in macrophage polarization, chronic inflammation, and organ fibrosis in different organs, highlight the potential role of macrophage autophagy in the treatment of fibrosis. Finally, the important unresolved issues in this field are briefly discussed. A better understanding of the mechanisms that macrophage autophagy in macrophage polarization, chronic inflammation, and organ fibrosis may contribute to developing novel therapies for chronic inflammatory diseases and organ fibrosis.